2022
DOI: 10.3390/nu14102096
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics and the Human Gut Microbiota: From Breakdown Mechanisms to the Impact on Metabolic Health

Abstract: The colon harbours a dynamic and complex community of microorganisms, collectively known as the gut microbiota, which constitutes the densest microbial ecosystem in the human body. These commensal gut microbes play a key role in human health and diseases, revealing the strong potential of fine-tuning the gut microbiota to confer health benefits. In this context, dietary strategies targeting gut microbes to modulate the composition and metabolic function of microbial communities are of increasing interest. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 164 publications
0
17
0
Order By: Relevance
“…When the fiber bundle was added at lower levels (1%, 2%, or 4% w/w), significant increases in straight-chain SCFAs were observed with the fiber bundle added to 4%, and concentrations of several polyphenols were significantly higher with addition of any level of the fiber bundle [11]. These results may indicate positive health effects since SCFAs show several benefits to the host such as serving as an energy source, maintaining the integrity of the intestinal barrier, contributing to whole-host metabolism via fueling of hepatic biosynthesis pathways, and serving as signaling molecules [12]. However, no changes in the fecal microbiota were observed [11].…”
Section: Introductionmentioning
confidence: 92%
“…When the fiber bundle was added at lower levels (1%, 2%, or 4% w/w), significant increases in straight-chain SCFAs were observed with the fiber bundle added to 4%, and concentrations of several polyphenols were significantly higher with addition of any level of the fiber bundle [11]. These results may indicate positive health effects since SCFAs show several benefits to the host such as serving as an energy source, maintaining the integrity of the intestinal barrier, contributing to whole-host metabolism via fueling of hepatic biosynthesis pathways, and serving as signaling molecules [12]. However, no changes in the fecal microbiota were observed [11].…”
Section: Introductionmentioning
confidence: 92%
“…Gut bacteria break down complex polysaccharides through the expression of a large panel of carbohydrate-active enzymes (CAZymes). Dietary fiber consumption increases the relative abundance of bacteria with CAZyme-encoding genes [ 39 , 40 ]. However, the changes in microbiota composition depend on the type of fiber used.…”
Section: Biological Effects Of Pectinmentioning
confidence: 99%
“…It has been shown that a diet high in refined or processed starches and sugars that have lost the majority of fibers (~40% insoluble dietary fiber) and nutrition value can produce substantial swings in blood glucose and insulin levels, 23,24 proceed TG accumulation, the key driver of central obesity triggering adipocytokine dysregulation, and generation of inflammation, IR, MetS, and cardio‐metabolic complications 25,26 . On the other hand, complex CHO, that is, slowly digestible, such as whole grain, bran, as well as nondigestible and lente CHO have been shown to improve postprandial insulinemia, gut satiety peptides, gut microbiota, hyperlipidemia, lean body mass, inflammation and, ultimately, lower the prevalence of MetS and T2DM 27–30 . Recently short‐chain fatty acids (SCFAs) derived from dietary fibers have been used as potential therapeutic targets in the management of various metabolic disorders 27–31 .…”
Section: Introductionmentioning
confidence: 99%
“…25,26 On the other hand, complex CHO, that is, slowly digestible, such as whole grain, bran, as well as nondigestible and lente CHO have been shown to improve postprandial insulinemia, gut satiety peptides, gut microbiota, hyperlipidemia, lean body mass, inflammation and, ultimately, lower the prevalence of MetS and T2DM. [27][28][29][30] Recently short-chain fatty acids (SCFAs) derived from dietary fibers have been used as potential therapeutic targets in the management of various metabolic disorders. [27][28][29][30][31] For example, SCFAs (acetate, propionate, and butyrate) are the main metabolic products of gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation